Peat oxic and anoxic controls of Sphagnum decomposition rates in the Holocene Peatland Model decomposition module estimated from litterbag data - H. Teickner; H. Teickner; E. Pebesma; K.-H. Knorr (Earth System Dynamics)
The Holocene Peatland Model (HPM) is a widely applied model for understanding and predicting long-term peat accumulation, but it is difficult to test due to its complexity, measurement errors, and lack of data. Instead of testing the complete model, tests of individual modules may avoid some of these problems. In particular, the HPM decomposition module can be tested with litterbag data, but no such test has been conducted yet.